Artificial & composite materials based on wideband structure for antenna profile reduction. (2021) - Sakthisudhan, K.; Vinothini, V.R.; Nandhakumar, S.; Saranraj, N.; SenthilKumar, R.
Abstract: An array of 6 × 6 Jerusalem cross shaped MPAs fed using microstrip transmission line is presented. It consists of the patch strip dimension of 54 × 54 mm 2, resonant frequency of 4.583 GHz and FBW of 46.67% against which return loss characteristics are achieved with transmission line components. These fabricated MPA prototypes have superior results and justified simulation design and provides the enhanced MPAs design and strategies than the prior MPAs designs. The main contribution of a 6 × 6 array of enhanced JC MPAs is the use of wider band coverage, tuned at UWB frequency and Artificial Magnetic Conductors (AMC). The 6 × 6 array of JC MPAs prototypes offer the FBW of 46.67%.